Compact zeroth-order resonator (ZOR) antennas - Lee Jae-Gon; Lee Jeong-Hae (EPJ Applied Metamaterials, 2019)
In this paper, we introduce and review the zeroth-order resonator (ZOR) antennas with outstanding characteristics including various applications that have been researched so far. Since the zeroth-order resonance frequency is independent of a physical length of antenna, the ZOR antenna can theoretically be designed quite small and have a possibility to apply to considerably lots of applications. First, we have presented the ZOR antennas implemented by double-negative (DNG), epsilon-negative (ENG), and mu-negative (MNG) transmission lines. Then, the research related on extremely small, wide beamwidth, wideband, and circularly polarized (CP) ZOR antennas have been continuously carried out. Based on a series of these studies, the ZOR antennas were utilized for various applications such as a wireless power transfer (WPT), a compact controlled reception pattern antenna (CRPA), a penta-band mobile antenna, and a wide steering array antenna.